Examining the Performance of Agriculture in the Economy of the Philippines Evidence from the Regional Panel - Paraguison, Joynabel S.; Associate Professor Genelyn Ma. F. Sarte (2024)
ABSTRACT

This study examines the performance of agriculture, as measured by Gross Value Added in Agriculture, Forestry and Fishing (GVA AFF) and the growth rates of GVA AFF, of the 16 regions of the country (excluding NCR) from 2005 to 2022. The researcher primarily aimed to established the link between regional performance of agriculture and selected social, macro economic, and environmental factors. The models are expected to supply information and insights on the factors that contribute to the performance of agriculture.

This research employed three (3) estimations methods, namely the Pooled Ordinary Least Squared estimation, Fixed Effects estimation, and Random Effects estimation One (1) model for GVA AFF and one (1) model for growth rates of GVA AFF were then selected based on the value of Adjusted R-square and Rho.

For the GVA AFF as the dependent variable, the final model was estimated through Random Effects estimation. This model was formulated to identify the factors that influence the absolute level of GVA AFF across different regions and periods.

Meanwhile, Fixed Effects models was estimated for the growth rate of GVA AFF. This model was formulated to determine the factors that influence the agriculture's growth trajectory (i.e., how fast the agriculture is rising or failing over a certain period).

The results suggested that palay yield per hectare, number of rural and and cooperative banks, proportion of employed persons in AFF, and the algorithm of the budget allotted for agriculture, positively impact the GVA and AFF. On the other hand, the proportion of rural population, and the logarithm of average land area received by CARP beneficiaries have negative linear relationship with GVA AFF.

Moreover, this study revealed that algorithm of the yield of palay per hectare and logarithm of the proportion of rural population have positive linear relationship with the growth rates of FGA AFF. The inflation rate of food, the African Swine Fever (ASF) indicator, logarithm of the budget allotted for agriculture, and logarithms of the value of damages in agriculture due to natural events and disasters were found to contribute to the growth rates of GVA AFF negatively.

Further, the significance of crude death rate, irrigation service area, and number of tropical cyclones (i.e., number of tropical depressions, storms, and typhoons) was not confirmed on this study.
Includes bibliographic reference.
Keywords: Panel Data Analysis -- Pooled Ordinary Least Squares -- Fixed Effects Estimation -- Random Effects Estimation -- Gross Value Added in Agriculture and Fisheries